POLITIK HUKUM PEMBENTUKAN UNDANG–UNDANG DENGAN METODE OMNIBUS LAW BERDASARKAN SISTEM HUKUM INDONESIA - Karo Karo, Josua Banta; Indra, Mexsasai; Lestari, Maria Maya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Indonesia applies the concept of the omnibus law in drafting laws. Omnibus law is a concept of making regulations that combines several rules with different regulatory substances, into one regulation under one legal umbrella. However, in the drafting process there were several irregularities that occurred such as the exclusion of public participation and a closed and hasty process which was contrary to Article 5 of Law of the Republic of Indonesia Number 15 of 2019 concerning Amendments to Law Number 12 of 2011 concerning Establishment. LegislationThis type of legal research is normative legal research. The normative legal approach used in this study is the statute approach, while this research is descriptive in nature.The result of this research is the legal politics of the formation of laws using the omnibus law method based on the Indonesian legal system, namely that the discussion was carried out in a hurry so that it collided with other laws, there was no government effort to involve the public, especially from civil society organizations and labor unions. The formulation of the Job Creation Bill is not transparent and lacks openness. The procedure for the formation of laws using the omnibus law method based on the Indonesian legal system, namely in the hierarchy of the order of laws and regulations in Indonesia as stipulated in the Law of the Republic of Indonesia Number 15 of 2019 does not include the omnibus law method as one of the principles in legal sources as well as a methodological framework for revising statutory regulations.Keywords: Political Law, Omnibus Law, Indonesian Legal System